A Case Study of Complex Policy Design: The Systems Engineering Approach. (3rd January 2019) - Buzuku, Shqipe; Farfan, Javier; Harmaa, Kari; Kraslawski, Andrzej; Kässi, Tuomo
Abstract : Design, structure, modelling, and analysis of complex systems can significantly benefit from a systematic approach. One way to address a complex system using a systematic approach is to combine creative and analytical methods, such as general morphological analysis and design structure matrix. The aim is to propose a framework to address complex systems in two stages: first, formulation and generation of alternatives through general morphological analysis, and second, improvement and integration with design structure matrix for sequence optimization and cluster analysis. Moreover, general morphological analysis is further optimized through a novel sensitivity analysis approach reducing up to 80% the iteration time. The proposed approach is showcased in a case study of sustainable policy formulation for a wastewater treatment plant at a pulp and paper industry in Brazil. The results show that it is possible to generate a solution space that highlights the best possible combinations of the given alternatives while also providing an optimal sequence and grouping for an optimized implementation. The paper contributes to the field of conceptual modelling by offering a systematic approach to integrate sustainability.